LEGAL PROTECTION OF A TRADEMARKS FROM DEEP LINKING IN THE DIGITAL WORLD - Ananda Fersa Dharmawan; Dea Rahmawaty Ruhiat; Muhamad Amirulloh (Fakultas Hukum Universitas Padjadjaran, 2023)
Issues surrounding the practice of deep linking as brand infringement represent a new transformation in the form of digital brand infringement. Legal protection against new forms of digital trademark infringement is urgently needed in order to protect brands as intellectual property rights in the ICT era. The approach method used in this research is normative juridical by using secondary data in the form of literature on laws and regulations, books and articles related to deep linking and brands. From the exposure and discussion of the act of deep linking of a brand digitally which is studied through the analysis in this article, it can be concluded that the theory and legal principles used in underlying the formation of a trademark protection law from deep linking as a trademark violation on the internet include the theory of brand protection in the era of ICT, the theory of development law and the theory of economic analysis of law (economic analysis of law). The principles that can underlie the law on trademark protection from deep linking include the Droit de Suite principle and the Good Faith principle. As a legal basis for civil lawsuits and criminal prosecution of deep linking of current brands, the articles contained in the ITE Law can be used because Law Number 20 of 2016 concerning Marks and Geographical Indications does not yet regulate deep linking.